Genome-Wide Identification and Characterization of Salvia miltiorrhiza Laccases Reveal Potential Targets for Salvianolic Acid B Biosynthesis - Li, Qing; Feng, Jingxian; Chen, Liang; Xu, Zhichao; Zhu, Yingjie; Wang, Yun; Xiao, Ying; Chen, Junfeng; Zhou, Yangyun; Tan, Hexin; Zhang, Lei; Chen, Wansheng (Frontiers in Plant Science, 2019)
Laccases are widely distributed in plant kingdom catalyzing the polymerization of lignin monolignols. Rosmarinic acid (RA) has a lignin monolignol-like structure and is converted into salvianolic acid B (SAB), which is a representatively effective hydrophilic compound of a well-known medicinal plant Salvia miltiorrhiza and also the final compound of phenolic acids metabolism pathway in the plant. But the roles of laccases in the biosynthesis of SAB are poorly understood. This work systematically characterizes S. miltiorrhiza laccase (SmLAC) gene family and identifies the SAB-speciﬁc candidates. Totally, 29 laccase candidates (SmLAC1-SmLAC29) are found to contain three signature Cu-oxidase domains. They exhibit relatively low sequence identity and diverse intron-exon patterns. The phylogenetic clustering of laccases from S. miltiorrhiza and other ten plants indicates that the 29 SmLACs can be divided into seven groups, revealing potential distinct functions. Existence of diverse cis regulatory elements in the SmLACs promoters suggests putative interactions with transcription factors. Seven SmLACs are found to be potential targets of miR397. Putative glycosylation sites and phosphorylation sites are identified in SmLAC amino acid sequences. Moreover, the expression profile of SmLACs in different organs and tissues deciphers that 5 SmLACs (SmLAC7/8/20/27/28) are expressed preferentially in roots, adding the evidence that they may be involved in the phenylpropanoid metabolic pathway. Besides, silencing of SmLAC7, SmLAC20 and SmLAC28, and overexpression of SmLAC7 and SmLAC20 in the hairy roots of S. miltiorrhiza result in diversification of SAB, signifying that SmLAC7 and SmLAC20 take roles in SAB biosynthesis. The results of this study lay a foundation for further elucidation of laccase functions in S. miltiorrhiza, and add to the knowledge for SAB biosynthesis in S. miltiorrhiza.